G204(P) Can Taurolidine-Based Catheter Locks Reduce Central Venous Catheter Related Blood Stream Infections In Children On Long-Term Home Parenteral Nutrition?. (4th June 2013) - Howarth, L; Gaynor, E; Rodrigues, A; Sullivan, PB
Abstract : Objectives and study: To compare the incidence and characterise the type of catheter-related blood stream infections (CRBSIs) in children with intestinal failure on long-term home parenteral nutrition (PN), using heparin-saline based catheter locks versus those using taurolidine-based catheter locks. There is growing body of evidence that taurolidine-based catheter locks, which have a broad-spectrum antimicrobial and antifungal action, is associated with a decreased incidence of CRBSIs children on home PN. Methods: All children referred to a tertiary paediatric gastroenterology service with temporary or on-going intestinal failure requiring long-term PN or preparation for home PN between 2005–2011 were included. Children were given a single-bag system of PN with each infusion via central venous catheter. Parents were formally trained in aseptic techniques and to instil heparin-saline or taurolidine-based solution into the catheter after completion of each infusion. CRBSIs were defined as a laboratory-confirmed blood stream infection from with a peripheral or central venous sample. Results were excluded if evidence that the source of infection was from a second site. All cultures results were confirmed through the microbiology database and clinical records. Research ethics committee approval was sought, but ethical review was not deemed necessary. Results: 32 children (18 boys, 14 girls) were identified who required PN for intestinal failure for combined total of over 12, 500 PN days. 9 children had no positive blood cultures. There were 126 positive blood cultures (27 organisms isolated) in the remaining 23 children. Of the 21 children who used a heparin-saline based catheter lock, 86% had one or more CRBSI. 11 children used a taurolidine-based catheter lock, with only 45% having one or more CRBSI. Conclusion: There was a significant reduction in the incidence of CRBSIs in those children using taurolidine-based catheter locks (TauroLock™) compared to heparin locks. There was an absolute risk reduction of 40.3% (95% CI 7.25 – 73.3%) with a numbers needed to treat (NNT) of 3 (95% CI 1.4–13.8). The use of taurolidine locks on all children on long-term home PN could reduce morbidity and morality, and have a significant impact on the associated costs of CRBSIs. Taurolidine-based catheter locks should be considered for all children on long-term PN.